2017
DOI: 10.17240/aibuefd.2017.17.32772-364008
|View full text |Cite
|
Sign up to set email alerts
|

6. Sınıf Sosyal Bilgiler Ders Kitabının Farklı Okunabilirlik Formüllerine Göre İncelenmesi

Abstract: Okunabilirlik formülleri metnin gözlenebilen dilsel özelliklerinden yola çıkarak metinleri okuma zorluklarına veya kolaylıklarına göre aşamalı olarak sınıflandırmayı amaçlayan kestirim araçlarıdır. Ders kitabının okunabilirliğinin seviyeye uygun olması, konuların öğrenciler açısından kolay anlaşılmasını sağlayacaktır. Çalışmada yedi farklı yayınevine ait ortaokul 6 sınıf Sosyal Bilgiler ders kitabının okunabilirliği ölçümü ve hedef yaş kitlesine uygun olup olmadığı saptanmıştır. Araştırmanın modeli doküman inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
6
1
3
Order By: Relevance
“…We cannot find the opportunity to do enough activities in 2 lesson hours, and this negatively affects the reinforcement of our course, which consists mostly of abstract subjects, in students" (Insufficient lesson hours)) is in parallel with the results of many studies on this subject in the literature. (Demirkaya and Karacan;Erol, 2016;Sönmez and Yıldırım, 2015;Tangülü, Tosun and Kocabıyık;Çelik and Katılmış, 2010;Palandökenliler, 2008;Ulu Kalın, 2007). Another prominent finding in the research is "The number of questions pertaining to the course in the LGS exam is low" and in the study titled "Examination of TEOG and LGS Systems from the Perspectives of Students, Teachers, Parents and Teacher-Parents" by Kuzu and Gelbal (2019), it was concluded that there were 20 questions each were asked from Turkish, Mathematics and Science courses, and that 20 questions were sufficient.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…We cannot find the opportunity to do enough activities in 2 lesson hours, and this negatively affects the reinforcement of our course, which consists mostly of abstract subjects, in students" (Insufficient lesson hours)) is in parallel with the results of many studies on this subject in the literature. (Demirkaya and Karacan;Erol, 2016;Sönmez and Yıldırım, 2015;Tangülü, Tosun and Kocabıyık;Çelik and Katılmış, 2010;Palandökenliler, 2008;Ulu Kalın, 2007). Another prominent finding in the research is "The number of questions pertaining to the course in the LGS exam is low" and in the study titled "Examination of TEOG and LGS Systems from the Perspectives of Students, Teachers, Parents and Teacher-Parents" by Kuzu and Gelbal (2019), it was concluded that there were 20 questions each were asked from Turkish, Mathematics and Science courses, and that 20 questions were sufficient.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Likewise, the difficulty levels of the texts differ from each other. While students can easily read some texts in textbooks, they may have difficulty with some texts (Ulu Kalın & Aydemir, 2017). Overlapping the reading levels of the texts with the reading levels of the students will make the texts easy to understand (Ulusoy, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted in the literature so that the texts in the textbooks can be easily understood by students (Çeçen & Aydemir, 2011;Gül et al, 2020;Ulu Kalın & Aydemir, 2017). In these studies, it was tried to determine the suitability of the texts to the reader level with the help of formulas that help to predict the reading level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitekim literatür incelendiğinde yapılan bazı çalışmalarda aynı kitabın içerisindeki metinler hem yabancı menşeili formüllerle hem de Türkçeye uyarlanan formüllerle değerlendirildiğinde farklı sonuçlara ulaşıldığı görülmüştür (Çakmak ve Çil, 2014;Geçit, 2010 Literatür incelendiğinde başta Türkçe ders kitaplarının okunabilirliği (Baş ve İnan Yıldız, 2015;Çakıroğlu, 2015;Çiftçi ve diğ., 2007;Okur ve Arı, 2013;Yılmaz ve Temiz, 2014;Zorbaz, 2007) olmak üzere farklı derslere ait ders kitaplarının okunabilirlik düzeylerine ilişkin birçok çalışma yapıldığı görülmektedir (Arnsdorf, 1963;Çakmak ve Çil, 2014;Çetinkaya, Yenmez, Çelik ve Özpınar, 2018;Dukes ve Kelly, 1979;Eker, İnce ve Sağlam, 2018;Hidayat, 2016;Hippensteel, 2015;Kaya, 1998;McConnell, 1982;Özay Köse, 2009;Ruscher, 1984;Schneider, 2011;Tekbıyık, 2006;Topkaya ve diğ., 2015;Ulu Kalın ve Koçoğlu, 2017). Bununla birlikte konuya ilişkin çalışmaların genel olarak ilk ve ortaokul ders kitaplarına yoğunlaştığı, ortaöğretimde kullanılan ders kitaplarının okunabilirliğini inceleyen çalışmaların ise nispeten daha sınırlı olduğu dikkat çekmektedir.…”
Section: Introductionunclassified